2015
DOI: 10.1016/j.tet.2015.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-substituted dimethylbenzimidazolines as effective reductants of photoinduced electron transfer reactions

Abstract: a b s t r a c tPhotoinduced electron transfer (PET) reactions promoted by 2-aryl substituted 1,3-dimethylbenzimidazolines (Ar-DMBIH) were investigated. Excited states of Ar-DMBIH, formed by irradiation using light above 360 nm, initiate PET reductions of various organic substrates, including transformations of epoxy ketones to aldols, free radical rearrangements such as the Dowd-Beckwith ringexpansion and 5-exo hexenyl cyclization, deprotection of N-sulfonyl-indols, and allylation of acyl formates. In these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…BIH and BI­(OH)H have much stronger reducing power (BIH: E 1/2 ox = 0.33 V; BI­(OH)­H: E 1/2 ox = 0.31 V vs SCE) compared to that of the NADH model compounds. Owing to this property, both compounds efficiently quenched the excited state of the Ru photosensitizer unit in the supramolecular photocatalysts (for example, k q = 9.7 × 10 8 M –1 s –1 , η q = 99% for RuRe12 with BIH (0.1 M)) (Process II). , Irradiation of a mixed solution of DMF-TEOA containing RuRe12 and BIH (0.1 M) induced the selective catalytic formation of CO with much greater efficiency, durability, and rate of CO formation (entry 23: Φ CO = 0.45, TON CO = 3029, TOF CO = 35.7 min –1 ) compared with those using BNAH (entry 22: Φ CO = 0.15, TON CO = 207, TOF CO = 4.7 min –1 ) . The efficiency and durability of the photocatalysis using RuRe15 were also much improved by using BIH (entry 27: Φ CO = 0.54, TON CO = 2915) instead of BNAH (entry 26: Φ CO = 0.13, TON CO = 233).…”
Section: Sacrificial Electron Donorsmentioning
confidence: 99%
“…BIH and BI­(OH)H have much stronger reducing power (BIH: E 1/2 ox = 0.33 V; BI­(OH)­H: E 1/2 ox = 0.31 V vs SCE) compared to that of the NADH model compounds. Owing to this property, both compounds efficiently quenched the excited state of the Ru photosensitizer unit in the supramolecular photocatalysts (for example, k q = 9.7 × 10 8 M –1 s –1 , η q = 99% for RuRe12 with BIH (0.1 M)) (Process II). , Irradiation of a mixed solution of DMF-TEOA containing RuRe12 and BIH (0.1 M) induced the selective catalytic formation of CO with much greater efficiency, durability, and rate of CO formation (entry 23: Φ CO = 0.45, TON CO = 3029, TOF CO = 35.7 min –1 ) compared with those using BNAH (entry 22: Φ CO = 0.15, TON CO = 207, TOF CO = 4.7 min –1 ) . The efficiency and durability of the photocatalysis using RuRe15 were also much improved by using BIH (entry 27: Φ CO = 0.54, TON CO = 2915) instead of BNAH (entry 26: Φ CO = 0.13, TON CO = 233).…”
Section: Sacrificial Electron Donorsmentioning
confidence: 99%
“…In addition, since this process competes with the radiative and non-radiative deactivation processes from the excited state of a photosensitizer by itself, the shorter lifetime results in less opportunity of the reductive quenching process to occur. To evaluate whether reductive quenching occurs, the emission intensity from Ru(pic) was compared in the presence of five different concentrations of a sacrificial electron donor, 1,3-dimethyl-2-phenyl-2,3-dihydro-1 H -benzo[ d ]imidazole (BIH) (Tamaki et al, 2013a; Hasegawa et al, 2015) in DMA-triethanoamine (TEOA; 5:1 v/v). As shown in Figure 4, the emission intensities from the 3 MLCT excited state of Ru(pic) decreased at higher concentrations of BIH, which indicated that the excited Ru(pic) was quenched by BIH.…”
Section: Resultsmentioning
confidence: 99%
“…Photoinduced electron transfer (PET) promoted reactions are a powerful and environmentally friendly tool for the construction of complex organic molecules [1][2][3][4][5] and polymers [6,7] that cannot be prepared by other methods. This is due to the highly reactive radical cation and anion intermediates generated via PET, which facilitate oxidation and reduction reactions under mild conditions (e.g., at room temperature), utilizing light as a clean and traceless reagent.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the highly reactive radical cation and anion intermediates generated via PET, which facilitate oxidation and reduction reactions under mild conditions (e.g., at room temperature), utilizing light as a clean and traceless reagent. PET-promoted reactions using photoredox catalysts, such as transition-metals (Ru, Ir) [1][2][3][4][5]8] and Fukuzumi photocatalysts [1][2][3][4][5]9], are among the recent trends in organic synthesis (Scheme 1a). The Fukuzumi photocatalyst, in particular an electron donor-acceptor-linked dyad (9-mesityl-10-methylacridinium ion, Acr + -Mes) acts as an efficient organic photoredox catalyst due to the long-lived electron-transfer state formed upon irradiation.…”
Section: Introductionmentioning
confidence: 99%